SPATIAL DATABASES OF AGRONOMIC GEOINFORMATION SYSTEMS - Pavlova, Anna I. (Siberian journal of life sciences and agriculture, 2022)
The work is devoted to the development of spatial databases for the assessment of agricultural land. The geodatabase is aimed at geoinformation support of assessment, agroecological typing (groups, types of land) of agricultural lands, development of adaptive-landscape farming systems. The paper presents the structure of the database of regional and local levels. Three different ways of user interaction with the AgroGIS database are proposed. For practical implementation, it is proposed to use the object-functional approach to database development, based on the use of cloud data storage technology in the DBMS SQlite. Background. Geoinformation support of agronomic geoinformation systems (AgroGIS) is aimed at assessing natural-territorial conditions and environmental factors in agrolandscapes, development of adaptive landscape farming systems. AgroGIS geodatabases serve to store, analyze and present spatial information on agricultural land. As shown by an analysis of literary sources, the term “geodatabase” was formed more than twenty years ago. At the same time different geodatabases are known: archaeological, cartographic, soil and others. They differ in the object of research, structure and content, as well as the way of data organization. This indicates the relevance of the topics of the present research. Purpose. The purpose of the work is to develop the structure and content of the geodatabase agronomic GIS. Materials and methods. The object-functional approach to database development, which is supported by object-oriented database management systems (DBMS) and classical relational DBMS, is used. The essence of this approach is to implement functional tasks taking into account the needs of the user. Results. The main components of geodatabase in the form of separate sets of spatial classes (Climate, Relief, Soil, Vegetation, Hydrography, Agrolandscape) are proposed. At the same time the paper shows the need for practical implementation of agronomic geoinformation geodatabases from several aspects. Conclusion. In the development of spatial databases of agronomic GIS the most important feature is the ability to constantly update information in the form of temporal component. Practical implementation of temporal geodatabases is possible with the use of non-relational database management systems, as well as methods of processing big data (Big Data).